Teaching in Vocational Schools: Educational Alignment versus the Promotion of Talents - Koppitz, Tina (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Teaching and learning has fundamentally changed in the last thirty years. In this period, a wide range of novel teaching theories has been established. Recent research states that a teachers professional identity consists of a cognitive, psychological and also a social perspective. The identity of a teacher emerges when s/he interacts with his/her students or other people. As a result of these interactions, teachers treat the questions “who are they? and who do they want to become?. These questions pose different views on educational methodologies today. On the one side some professionals argue for learning in a community which supports establishing an average basis of knowledge among all pupils. This approach especially helps the struggling pupils, since a key component is that pupils learn from each other and align their knowledge. On the other side, however, others vote for an individual learning program. Here, in particular talents are promoted. The question is, what approach is more promising for the society of tomorrow. This work deals with the underlying theories, discusses the advantages and disadvantages of these learning theories and, as an example, additionally incorporates a focused view on the Austrian education system